(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The Teluk Bakau waters is known for its marine tourism and is often used as a traditional fishing ground. Information regarding sediment distribution in the Teluk Bakau waters is limited. Existing studies have only conducted sampling at specific locations, and there have been no reports on the spatial scattering characteristics of the sediment types on the seafloor in this area. The objective of this study is to analyze and map the acoustic backscatter values of each sediment type to obtain a spatial distribution map of sediments in the Teluk Bakau waters. The research was conducted in May 2023, using a survey method with the Simrad EK15 single-beam echosounder acoustic instrument set at a frequency of 200 kHz. Data collection in the field was done using survey lines, and during the acoustic data collection, sediment samples were collected using a sediment grab at five stations. The recorded acoustic data from the seabed were then extracted using EchoView 4.0 software to determine the values of volume backscattering strength (SV). The SV values were utilized to obtain the surface backscattering strength (SS) values, while the sediment samples were analyzed using gradistat 8.0 software. Based on the analysis conducted, Bakau Bay has SV values ranging from -34.00 dB to -38.48 dB. Based on the analysis of the SS values, Bakau Bay is dominated by coarse sand sediments in both the tracking results and sediment sampling, with backscattering values ranging from -16.00 dB to -17.49 dB. Additionally, two sediment types are evenly distributed along the tracking lines medium sand with backscattering values ranging from -17.49 dB to -18.97 dB, and fine sand with backscattering values ranging from -19.26 dB to -20.57 dB, found at a depth of 14-16 meters.